Generalized phase calibration method of liquid crystal spatial light modulator with absolute reference system of obnoxious background light. (September 2020) - Li, You; Li, Yaocun; Zhang, Junyong; Li, Yangshuai; Wang, Zengkun; Yin, Changzhi; Zhang, Yanli; Zhou, Shenlei; Liu, Dean
Highlights: A single channel calibration method which utilized the inherent obnoxious background light of the spatial light modulator to provide calibration function is proposed. The background light can be used as an absolute coordinate system to improve system robustness. The proposed method here takes into account the advantages of interferometry and diffraction method, thus has the very strong adaptability for SLM calibration. Abstract: Spatial light modulators (SLMs) are widely used in many optical fields such as wavefront modulation, beam shaping and diffractive optical elements. It is necessary to calibrate SLM to determine the initial state of device before using it. Here a simple and generalized interferometry is proposed to calibrate the phase modulation curve with good robustness, stability and high precision, in which the obnoxious background light is no longer an undesired signal, but is utilized as an absolute reference system that provides the self-reference functionality. Combined with centroid localization algorithm, the phase modulation curve can be easily calculated by the fringes shift. Besides, multi-channel detector simultaneously provides three groups of data that further improve the calibration accuracy of gamma curve by weighted average algorithm. An experiment on phase-shifting holography was carried out and verified the validity of our proposed method. The larger the CCD target surface, the better the calibration accuracy is.